2021
DOI: 10.21203/rs.3.rs-658071/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal and Newborn Health for the Urban Poor: The Need for a New Mental Model and Implementation Strategies to Accelerate Progress

Abstract: Background: Urbanization challenges the assumptions that have traditionally influenced maternal and newborn health (MNH) programs. This landscaping outlines the ways in which current mental models for MNH programs have fallen short for urban slum populations, and identifies implications for the global community. We employed a three-pronged approach, including a literature review, key informant interviews with global- and national-level experts, and a case study in Bangladesh. Main Body: Our findings highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Further, literature shows that poor women, especially those living in informal settlements, might also receive poorer quality of care, encounter stigmatising attitudes and disrespectful care in health facilities. 43-45 Our additional analysis on the timing of deaths showed that a comparatively low percentage of neonatal deaths in core urban areas occurred on the day of birth compared to semi-urban and rural areas. Interpretation is difficult, but one explanation may be better access to emergency obstetric care including neonatal resuscitation in core urban compared to rural areas.…”
Section: Discussionmentioning
confidence: 90%
“…Further, literature shows that poor women, especially those living in informal settlements, might also receive poorer quality of care, encounter stigmatising attitudes and disrespectful care in health facilities. 43-45 Our additional analysis on the timing of deaths showed that a comparatively low percentage of neonatal deaths in core urban areas occurred on the day of birth compared to semi-urban and rural areas. Interpretation is difficult, but one explanation may be better access to emergency obstetric care including neonatal resuscitation in core urban compared to rural areas.…”
Section: Discussionmentioning
confidence: 90%
“…The primary healthcare systems in the developing world have been unable to adequately meet the essential health needs of the people living in the slums, especially related to their maternal and child health requirements (30). Moreover, during the Covid-19 pandemic, lack of primary health system preparedness and their suboptimal services, especially in the delivery of maternal and child health (MCH) and NCD treatment services, contributed to the further accentuation of the pre-existing health vulnerabilities amongst the people, especially living in slums (31).…”
Section: Introductionmentioning
confidence: 99%